Evolution of Entrepreneurial Judgment With Venture‐Specific Experience. (10th June 2016) - Uygur, Ugur; Kim, Sung Min
Abstract : Research summary: This study advances research on entrepreneurial cognition by investigating how entrepreneurial judgment evolves during new venture creation. We conceptualize entrepreneurial judgment as a cognitive process in the minds of entrepreneurs that operates on the causal map—i.e., a knowledge structure concerning what factors they believe will help the chances of profitability under uncertainty. At the time of initial epiphany, entrepreneurs construct cognitive causal maps, which guide resource allocation decisions. Over time, venture‐specific experience accumulates and entrepreneurial judgment evolves in response to their observations. Using a dataset of 524 nascent entrepreneurs, we find that entrepreneurs with more venture‐specific experiences have more selective judgments, and they have stronger conviction in those judgments. We also find that perceived uncertainty and cognitive dispositions of the individuals affect entrepreneurial judgment. Managerial summary: Entrepreneurs often have to exercise judgment due to limited information and resources when creating new businesses. Because they cannot effectively make progress in all aspects of a new venture at once, entrepreneurs choose the important success factors to focus on. Our findings suggest that it is important to understand the cognitive mechanisms underpinning their judgments. As entrepreneurs gain more experience with the venture, their chosen set of success factors narrows and their confidence increases. Additionally, their self‐efficacy and decisiveness encourage them to make stronger judgments. This may imply a precarious scenario because of the risk of overconfidence in their judgments. Similarly, investors are also advised to check if the entrepreneur's conviction is supported by accumulated experience in the context of the venture. Copyright © 2016 Strategic Management Society.